Success and Impact of the Learning Support Program in Tri Tunggal Jaya Village, Lampung - Surti Nur Utami (The Indonesian Institute of Science and Technology Research, 2024)
The Learning Support Program in Tri Tunggal Jaya Village is an initiative to reduce the impact of gadget addiction among children by providing beneficial educational alternatives. This program aims to enhance the academic, social, and emotional abilities of children through interactive learning and a holistic approach. During the program implementation, there was a significant decrease in children's gadget usage, from 5 hours per day to 2 hours per day. Evaluations also indicated a 15% improvement in academic grades and a 70% enhancement in English language proficiency. Moreover, the program successfully increased children's social skills by 75% and led to better emotional development, as reported by parents. The success of the Learning Support Program demonstrates its potential as an effective model in addressing gadget addiction issues in rural communities, emphasizing the importance of holistic education to support the comprehensive growth and development of children.